2022
DOI: 10.7759/cureus.29272
|View full text |Cite
|
Sign up to set email alerts
|

A Case Series of Spinal Infections Following COVID-19: A Delayed Complication

Abstract: Spinal infection in the form of tuberculous vertebral osteomyelitis or pyogenic spondylodiscitis is a commonly associated state of an immunodeficient host from various pathologies. For example, secondary infections can be seen following coronavirus disease 2019 (COVID-19). We report three cases of different forms of spinal infections that occurred as delayed complications to recent COVID-19 infection. The first case is a 60-year-old female who was diagnosed with an epidural abscess presenting with severe back … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…According to PRISMA diagram, the cases with fungal aethiology and the repots with bacterial SD and/or epidural abscess diagnosed over 12 weeks post-COVID-19 were excluded. [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to PRISMA diagram, the cases with fungal aethiology and the repots with bacterial SD and/or epidural abscess diagnosed over 12 weeks post-COVID-19 were excluded. [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both had received tocilizumab, supporting the role of both COVID-19-related and drug-induced immunosuppression along with preexisting clinical factors as the reasons for secondary bacterial infection. Mohamed Ramlee et al [17] reported three cases of delayed spinal infections following a recent SARS-CoV-2 infection up to three months before the diagnosis. It was not reported whether the patients received any immunosuppressive COVID-19 treatment.…”
Section: Discussionmentioning
confidence: 99%